Enhancing Prison Safety and Discipline: The Role of Dynamic Security Strategies at Kamiti Maximum Security Prison, Kenya (Global Journal of Human-Social Science, 2025)
Dynamic security is a relatively new strategy in treatment of offenders and management of penal institutions. It involves inculcation of positive staff-prisoner relationships and ensuring that the staff are aware of what is going on within the prison walls through application of up to standard surveillance techniques and open communication. However, despite its introduction in Kenyan prisons, its impact on inmates’ discipline and safe custody remains underexplored. A study was therefore conducted at Kamiti Maximum Security Prison to ascertain its impact on inmates’ discipline and safe custody among others. Guided by the rehabilitation theory of punishment, which emphasizes reform and reintegration, the descriptive survey research targeted the prisons staff and prisoners at the facility who were both selected through probability and non-probability sampling techniques and data collected from 193 participants by use of questionnaires and key informant interviews. Descriptive statistics were used in analysing quantitative data while qualitative data were thematically analysed. The study established that the majority of both prisoners and staff reported improvements in safe custody and reductions in disciplinary cases following the implementation of Dynamic Security measures. However, it was revealed that implementation of dynamic security faces behavioural barriers and resource constraints among others. The study concluded that dynamic security is central to the attainment of imprisonment goals at the institution and recommended its progressive implementation in all corrections facilities in Kenya.